Survival, treatment pattern, and treatment outcome in patients with cervical cancer metastatic to distant lymph nodes - Lin, Haoliang; Wang, Dongyan; Li, Hui; Wu, Chuling; Zhang, Fengqian; Lin, Zhongqiu; Yao, Tingting (Frontiers in Oncology, 2022)
BACKGROUND: Cervical cancer with nodal involvement beyond the pelvis was considered as distant nodal metastasis in the previous International Federation of Gynecology and Obstetrics staging system. With the improvement of cancer-directed therapies, some of these patients can receive curative treatment. Classifying them as distant metastasis may result in underestimation of their prognosis as well as undertreatment. However, limited research has been conducted on the survival and treatment pattern in distant lymphatic metastatic cervical cancer. OBJECTIVE: To investigate the survival, treatment pattern, and treatment outcome of patients with cervical cancer metastasized to distant lymph nodes (DLN) beyond the pelvis. METHODS: Patients with stage III-IV cervical cancer from 1988 to 2016 were identified using the Surveillance, Epidemiology, and End Results program. The cancer cause-specific survival (CSS) was analyzed using the Kaplan-Meier method, log-rank test, multivariable Cox proportional hazard regression, subgroup analysis, and propensity score-matched analysis. RESULTS: Of 17783 patients with stage III-IV cervical cancer, patients with distant nodal disease beyond the pelvis (n=1883; included para-aortic lymph nodes metastasis) had superior survival compared to those with pelvic organ invasion or with distant organ(s) metastasis (5-year CSS, 32.3%, 26.3%, and 11.5%, respectively; adjusted P<0.001). The T stage significantly affected the survival of patients with positive DLN (5-year CSS for T1, T2, and T3: 47.3%, 37.0%, and 19.8%, respectively, adjusted P<0.01). For patients with positive DLN, combination radiotherapy (external beam radiotherapy [EBRT] with brachytherapy) prolonged CSS compared to EBRT alone (5-year CSS, 38.0% vs 21.7%; propensity score-adjusted HR, 0.60; 95% CI 0.51-0.72; P<0.001). Despite the superiority of combination radiotherapy, EBRT was the most frequently used treatment after 2004 (483/1214, 39.8%), while the utilization of combination radiotherapy declined from 37.8% (253/669) during 1988 through 2003 to 25.2% (306/1214) during 2004 through 2016. CONCLUSION: Patients with cervical cancer metastasized to DLN have favorable survival compared to those with pelvic organ invasion or with distant organ(s) metastasis. Their prognosis is significantly affected by local tumor burden and local treatment. Adequate and aggressive local radiotherapy, such as image-guided brachytherapy, can be considered for these patients to achieve better outcomes.